(untitled) (Journal of the College of Basic Education, 2023)
The present study aims to construct a Teaching program proposed in the collection of material GIS and identifying its effectiveness on the 2nd year female students who are participating in the experiment al group at the Department of Geography, college of Education For Women, University of Baghdad. A Partial control experimental design which is a pre – post experimental – control design is adopted in the present study. Two groups are assigned randomly as an experimental group which is section A , and a control group which is section B from the Deportment of Geography at the college of Education for Women . The total number It amounted research sample (60) by a student (30) students in each division. The two groups are equalized in several Factors which are : IQ lest , Age in months , prior knowledge , And testing of the above information for geographic information systems (pre-test), and academic achievement for parents, as well as several intruding factors are also controlled during the experimental work